2016
DOI: 10.3109/08958378.2016.1163441
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary sensitivity to ozone exposure in sedentary versus chronically trained, female rats

Abstract: Epidemiological data suggest that a sedentary lifestyle may contribute to increased susceptibility for some environmental toxicants. We developed an animal model of active versus sedentary life style by providing female Sprague-Dawley rats with continuous access to running wheels. Sedentary rats were housed in standard cages without wheels. After training for 12 wks, rats were exposed to 0, 0.25, 0.5 or 1.0 ppm ozone [O3 for 5 h/d, 1 d/wk, for 6 wk (N = 10 per group)]. Body composition (%fat, lean and fluid) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…We found a significant increase in Penh after the first and second exposure to 1.0 ppm ozone; however, there was no effect of exercise training on this this response. This was surprising since we recently reported that the ozone-induced rise in Penh of Sprague-Dawley rats exhibited a beneficial effect in response to exercise training (11). In that study, Penh was measured the day after ozone exposure.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…We found a significant increase in Penh after the first and second exposure to 1.0 ppm ozone; however, there was no effect of exercise training on this this response. This was surprising since we recently reported that the ozone-induced rise in Penh of Sprague-Dawley rats exhibited a beneficial effect in response to exercise training (11). In that study, Penh was measured the day after ozone exposure.…”
Section: Discussionmentioning
confidence: 87%
“…Overall, rats were studied in blocks of 20 each day over a 1-wk period with all animals exposed to ozone, tested for ventilatory function and glucose tolerance, and terminated. We chose a maximum ozone concentration of 1.0 ppm with the expectation that this concentration in other rat strains would evoke profound pulmonary inflammatory responses as we have shown in previous studies using concentrations of 0.8 -1.0 ppm (11,12). The lower concentrations were selected to develop a doseresponse.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…21 Additional studies have investigated the role of diet and sedentary behavior on ozone exposure responses. 42,43 …”
Section: Introductionmentioning
confidence: 99%